Engineering and Geological Zoning of the Residual Soil of the Malmyzhskoe Deposit (Svoboda Site) - I. V. Abaturova; T. S. Bobina (Vestnik Permskogo Universiteta: Seriâ Geologiâ, 2021)
Interest to the study of residual soil arose at a time when geological engineers faced the problem of developing the open pits in the eluvial soils. A significant number of Russian and foreign scientists considered the formation of weathering crusts from different points of view. They established the geochemical zoning, and engineering-geological zoning of the weathering crusts. However, no comprehensive and detailed engineering-geological zonation of the crusts of weathering, especially when studying mineral deposits, was given due to the insufficient attention paid to it until today. Therefore, it is important to correctly determine the type and profile of the residual soil in order to establish the possibility to control the engineering and geological conditions when exposing the rock mass during excavation work for further forecasting the slope stability of the projected open pit mining structures.